Adrenal Insufficiency: A Forgotten Diagnosis in HIV/AIDS Patients in Developing Countries - David D. Nassoro; Mkhoi L. Mkhoi; Issa Sabi; Alfred J. Meremo; Paul S. Lawala; Issakwisa Habakkuk Mwakyula (International Journal of Endocrinology)
Adrenal insufficiency (AI) is one of the most common endocrine disease in patients with HIV/AIDS, leading to high morbidity and mortality in HIV patients who become critically ill. Various etiologies are associated with the condition, including cytomegalovirus (CMV), Mycobacterium tuberculosis, lymphoma, Kaposi’s sarcoma, and drugs such as rifampin, among others. HIV patients with advanced disease develop relative cortisol deficiency largely due to the reduction of cortisol reserve, which predisposes patients to adrenal crisis in periods of stress or critical illness. The prevalence of AI in HIV/AIDS patients during HAART era is higher in developing than developed countries, probably due to limited access to both diagnosis and adequate treatments which increases the risk of opportunistic infections. The clinical features of functional adrenal insufficiency in HIV/AIDS patients can be masked by various infectious, noninfectious, and iatrogenic causes, which reduce clinical recognition of the condition. Development of simple screening algorithms may help clinicians reach the diagnosis when approaching these patients. In many low-income countries, most HIV patients are diagnosed with advanced disease; thus, further research is necessary to elucidate the prevalence of adrenal insufficiency in HIV/AIDS patients and the condition’s impact on mortality in this population.